Relationships between respiratory and oromotor events differ between motor phenotypes in patients with obstructive sleep apnea - Mutsumi Okura; Mutsumi Okura; Mutsumi Okura; Takafumi Kato; Midori Mashita; Hisae Muraki; Hisae Muraki; Hideko Sugita; Motoharu Ohi; Mitsutaka Taniguchi (Frontiers in Neurology, 2023)
PurposeThe present study investigated the relationship between sleep bruxism (SB) and obstructive sleep apnea (OSA) in relation to the sleep architecture.MethodsWe conducted a cross-sectional study. Polysomnographic recordings were performed on 36 patients. Sleep, respiratory, and oromotor variables, such as rhythmic masticatory muscle activity (RMMA) and non-specific masticatory muscle activity (NSMA), were compared between OSA patients with or without SB. A correlation analysis of the frequency of respiratory and oromotor events in NREM and REM sleep was performed. The frequency of oromotor events following respiratory events was also assessed.ResultsThe proportion of REM sleep was higher in OSA patients with SB than in those without SB (p = 0.02). The apnea-hypopnea index (AHI) did not significantly differ between the two groups; however, AHI was approximately 8-fold lower during REM sleep in OSA patients with SB (p = 0.01) and the arousal threshold was also lower (p = 0.04). Although the RMMA index was higher in OSA patients with than in those without SB (p < 0.01), the NSMA index did not significantly differ. The percentage of RMMA following respiratory events was significantly higher in OSA patients with than in those without SB, whereas that of NSMA did not significantly differ. The frequency of oromotor events throughout the whole night positively correlated with AHI. However, regardless of the sleep state, AHI did not correlate with the RMMA index, but positively correlated with the NSMA index.ConclusionIn consideration of the limitations of the present study, the results obtained indicate that OSA patients with SB have a unique phenotype of OSA and also emphasize the distinct relationship of respiratory events with RMMA and NSMA.